Regenerative Medicine Therapy in Malaysia: An Update - Imran, Siti A. M.; M. Hamizul, M. Haikal Aiman; Khairul Bariah, Ahmad Amin Noordin; Wan Kamarul Zaman, Wan Safwani; Nordin, Fazlina (Frontiers in Bioengineering and Biotechnology, 2022)
Regenerative medicine is a field in medicine that relates to the ability to correct congenital flaws and to repair or replace tissues and organs that have been destroyed by age, disease, or trauma. To date, promising preclinical and clinical data supported the possibility of using regenerative medicine to treat both chronic diseases and acute insults, as well as maladies affecting a wide range of organ systems and contexts, such as dermal wounds, cardiovascular diseases and traumas, cancer treatments, and more. One of the regenerative medicine therapies that have been used widely is stem cells. Stem cells, especially mesenchymal and hematopoietic stem cells, play an important role to treat chronic diseases, such as leukemia, bone marrow, autoimmune disease, and urinary problems. Despite considerable advancements in stem cell biology, ethical concerns about embryonic stem cells, tumor development, and rejection limit their application. Many of these constraints, however, are being overcome, which could lead to significant advancements in disease management. This review discusses the regenerative medicine therapy (RMT) advancements in Malaysia compared to other Asian countries, the current developments of RMT in Malaysia as well as the limitations in its application.